DEVELOPING MATHEMATICAL LOGICAL INTELLIGENCE THROUGH COOPERATIVE LEARNING MODEL TYPES OF TEAMS GAMES TOURNAMENT FOR STUDENT - Bintang Fahlia Lestari; Conny Dian Sumadi; Elvina Octavia; wijining Wulan Suci; Ineke Putri Wicandra (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Logical-mathematical intelligence for a student is related to the student's ability to calculate, measure, and complete mathematical operations. This study aims to see whether there is an effect of the team games tournament (TGT) cooperative learning model to develop logical-mathematical intelligence on the learning outcomes of third grade students at SDN Kedung Peluk 1 Candi. The approach used in this research is a quantitative approach. This type of research is associative research. The population in this study, amounted to 21 students of class III. There are two methods used to collect data in this research technique, namely: test and observation. Based on the results of data analysis, this study shows that there is a positive and significant influence on mathematical logical intelligence on student learning outcomes, using the team games tournament (TGT) cooperative learning model with the help of bingo, third grade students at SDN Kedung Peluk 1 Candi get with an average score of 96 with fractions math material.